Anmeldelser - Hogwood, Christopher (Danish Yearbook of Musicology, 2008)
Review of: F.L.Ae. Kunzen, Gesammelte Klavierwerke / Samlede klaverværker, ed. Gorm Busk and Heinrich W. Schwab. Capella hafniensis editions, series K, 1. Copenhagen: The Royal Library, 2004